Wage Centralization, Union Bargaining, and Macroeconomic Performance - McHugh, James (Washington, D.C. : International Monetary Fund, 2002)
This paper addresses two questions. First, under what circumstances will a centralized wage-bargaining system offer higher output and employment than a decentralized system? Second, what is the relationship between the degree of wage centralization and inflation? The paper argues that centralized wage setting may offer worse outcomes, despite the existence of a negative coordination externality in decentralized wage setting. This is more likely to occur when the legal and institutional environment strengthens the bargaining position of the union in the centralized regime compared with unions operating in a more decentralized regime. Furthermore, as product markets become more competitive, the macroeconomic outcomes in both regimes converge, and the degree of wage centralization becomes irrelevant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet